Anticompetitive Vertical Merger Waves - Johan Hombert; Jérôme Pouyet; Nicolas Schutz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2013)
We develop a model of vertical merger waves leading to input foreclosure. When all upstream firms become vertically integrated, the input price can increase substantially above marginal cost despite Bertrand competition in the input market. Input foreclosure is easiest to sustain when upstream market shares are the most asymmetric (monopoly-like equilibria) or the most symmetric (collusive-like equilibria). In addition, these equilibria are more likely when (i) mergers generate strong synergies; (ii) price discrimination in the input market is not allowed; (iii) contracts are public; whereas (iv) the impact of upstream and downstream industry concentration is ambiguous.
urn:nbn:de:bvb:19-epub-17399-4
Keywords: 330